2016
DOI: 10.1093/bib/bbw116
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling folate metabolism and DNA methylation: implications for understanding health and ageing

Abstract: Dietary folates have a key role to play in health, as deficiencies in the intake of these B vitamins have been implicated in a wide variety of clinical conditions. The reason for this is folates function as single carbon donors in the synthesis of methionine and nucleotides. Moreover, folates have a vital role to play in the epigenetics of mammalian cells by supplying methyl groups for DNA methylation reactions. Intriguingly, a growing body of experimental evidence suggests that DNA methylation status could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 138 publications
(127 reference statements)
0
20
1
Order By: Relevance
“…The essence of this approach is to utilise novel approaches to study molecules, cells or entire organisms. Nutrition research is no different and is beginning to benefit from this new paradigm (74)(75)(76)(77)(78)(79)(80) . It can be argued that electrochemical techniques come under this umbrella of systems techniques.…”
Section: Detecting Dna Methylationmentioning
confidence: 99%
“…The essence of this approach is to utilise novel approaches to study molecules, cells or entire organisms. Nutrition research is no different and is beginning to benefit from this new paradigm (74)(75)(76)(77)(78)(79)(80) . It can be argued that electrochemical techniques come under this umbrella of systems techniques.…”
Section: Detecting Dna Methylationmentioning
confidence: 99%
“…This framework provides a means of handling the complexities of hepatic cholesterol metabolism and ageing. Key to this approach is the use of mathematical models which enable the integration of disparate experimental data (49)(50)(51)(52).…”
Section: Investigating the Hypothesismentioning
confidence: 99%
“…FA plays a major role in two 1-carbon transfer pathways, including biological methylation reaction and nucleotide biosynthesis. Previous studies have proved that the deficiency of FA would result in inadequate DNA damage repair and impairs cellular proliferation by inducing aberrant DNA methylation, which increase the risk of various tumors [6][7][8]. Moreover, some studies also revealed that the supplementation of FA would significantly reduce inflammation and prevent the tumorigenesis of tumors by increasing global DNA methylation [5,9,10].…”
Section: Introductionmentioning
confidence: 99%